2019
DOI: 10.1002/jlcr.3717
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis of the norepinephrine transporter tracer [18F]NS12137 via copper‐mediated 18F‐labelling

Abstract: [ 18 F]NS12137 ( exo ‐3‐[(6‐[ 18 F]fluoro‐2‐pyridyl)oxy]8‐azabicyclo[3.2.1]octane) is a highly selective norepinephrine transporter (NET) tracer. NETs are responsible for the reuptake of norepinephrine and dopamine and are linked to several neurodegenerative and neuropsychiatric disorders. The aim of this study was to develop a copper‐mediated 18 F‐fluorination method for the production of [ 18 F]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, this aromatic core is electron-rich, hampering radiofluorination by standard aromatic nucleophilic substitution (Sn Ar ). Alternative approaches have been described using iodonium salts [ 21 , 22 , 23 ] or ylides [ 24 , 25 , 26 ] as precursors or by copper-catalyzed Cham-Lam-like fluorination using boronic acid [ 27 , 28 ], boronic ester [ 29 , 30 , 31 , 32 ], or trialkyltin precursors [ 33 , 34 ]. Late-stage isotopic radiolabeling of DTG was considered at the para position of the aromatic core (compared to the methyl amino group), as better radiochemical yields were depicted on this position compared to ortho [ 27 , 29 , 31 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, this aromatic core is electron-rich, hampering radiofluorination by standard aromatic nucleophilic substitution (Sn Ar ). Alternative approaches have been described using iodonium salts [ 21 , 22 , 23 ] or ylides [ 24 , 25 , 26 ] as precursors or by copper-catalyzed Cham-Lam-like fluorination using boronic acid [ 27 , 28 ], boronic ester [ 29 , 30 , 31 , 32 ], or trialkyltin precursors [ 33 , 34 ]. Late-stage isotopic radiolabeling of DTG was considered at the para position of the aromatic core (compared to the methyl amino group), as better radiochemical yields were depicted on this position compared to ortho [ 27 , 29 , 31 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a case-by-case optimization still seems to be necessary, being extremely difficult to reach a standardized procedure for every labeling precursor, which might explain the reason why the exact same methodology has been very rarely repeated in the literature. An analysis through the Cu-mediated works published, and hereby referenced [15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39], shows that [Cu(OTf) 2 (py) 4 ] is still by far the most common catalyst used (against other options such as Cu(OTf) 2 , Cu(OTf) 2 (associated with diverse pyridine derivatives), or Cu(CF 3 SO 3 ) 2 ), and the typical amounts for all of them are between 5 to 30 µmol while the Bpin labeling precursor may vary from 4 to 60 µmol. The reaction temperatures are usually kept around 120 °C ± 10 °C while anhydrous DMA and dimethylformamide (DMF) are the solvents almost exclusively reported, with the first one having the propensity for better conversion efficacies [39] which can arguably be due to its higher boiling point and resistance to bases.…”
Section: Discussionmentioning
confidence: 99%
“…One of these strategies, the late-stage copper-mediated oxidative 18 F-fluorination of arylboronic ester and acid derivatives, has received great attention from radiochemistry research groups but is still not routinely applied in the production of clinical PET radiopharmaceuticals. Numerous basic-research proposals for improving this Cu-catalyzed reaction have been successfully reported and conceptualized with simple heteroaromatic groups [15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33], but advanced applications to more complex molecules with potential clinical value are sparse and generally reveal very fluctuating 18 F-fluorination efficiencies [33,34,35,36,37,38]. Following previous work from our group [39], where we applied this Cu-mediated strategy to several structurally different drug-like molecules and investigated the influence of a range of temperature, solvents, catalyst, and precursor amounts, we aimed to go up in terms of complexity, applicability, and relevance.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Kirjavainen and co-workers prepared norepinephrine transporter tracer [ 18 F]NS12137 ( 70 ) via copper-mediated synthesis without a carrier from a stannylated precursor ( exo-tert -butyl-3-[(6-trimethylstannyl-2-pyridyl)oxy]-8-azabicyclo-[3.2.1]octane-8-carboxylate). 136 [ 18 F]NS12137 ( 70 ) was prepared in a two-step process including 18 F-radiofluorination, and deprotection by hydrolysis (Scheme 23). In the first step, stannane precursor 68 reacted with [ 18 F]KF·K 222 and Cu(OTf) 2 (py) 4 in DMA to provide intermediate [ 18 F] 69 with high radiochemical purity (>89%) and molar activity (up to 400 GBq μmol −1 ) after a 2-minute reaction at 120 °C.…”
Section: Radiofluorinationmentioning
confidence: 99%